Solving differential equations with Maple V, release 4 - David Barrow (Brooks/Cole Pub. Co., 1998)
This comprehensive book helps students tap into the power of Maple, thereby simplifying the computations and graphics that are often required in the practical use of mathematics. Numerous examples and exercises provide a thorough introduction to the basic Maple commands that are needed to solve differential equations. Topics include: numerical algorithms, first order linear systems, homogeneous and nonhomogeneous equations, beats and resonance, Laplace Transforms, qualitative theory, nonlinear systems, and much more.